PENYUSUNAN LAPORAN KEUANGAN DENGAN ACCURATE LITE UNTUK PENINGKATAN KEPATUHAN KEWAJIBAN PERPAJAKAN UMKM KABUPATEN BOGOR - Novitasari, Novitasari; Agha, Ridwan Zulpi; Ekowati, Lia; Nugroho, Herbirowo; Ichsan, Taufikul; Sixpria, Nedsal; Fatimah, Hayati; Aminah; Hafiduddin (Jurnal Abdi Insani, 2022)
ABSTRACT The lack of knowledge about transaction bookkeeping and the preparation of financial reports according to standards makes the level of MSME tax compliance in Bogor Regency is still relatively low. The existence of these problems made the group of lecturers in the field of Accounting expertise at the Jakarta State Polytechnic (PNJ) try to contribute in terms of education and assistance to the Micro, Small and Medium Enterprises (MSME) group of Bogor Regency in the form of training programs and assistance in preparing financial reports with MSEI standards (Micro Small Entities and Intermediate). This training activity aims to provide MSME actors with knowledge and skills in bookkeeping using the Accurate Lite application as an effort to improve MSME tax compliance. The training method uses case study methods and work instructions, where training materials are given in the form of cases and trainees carry out bookkeeping practices directly in the Accurate Lite application based on work instructions from tutors. As a result of the training activities, there was an increase in knowledge of accounting and taxation as well as an increase in the skills of the trainees in recording business transactions and compiling financial reports. Furthermore, it is hoped that the MSME players participating in the training can consistently do bookkeeping using the Accurate Lite application anywhere, anytime, not limited by space and time, because Accurate Lite can be downloaded on the device of each training participant. The conclusion of the activity is that the training activities that have been carried out have been able to improve participants’ accounting literacy so that participants can manage their business finances better in an effort to improve their tax compliance. Keywords: Training, Accounting, Tax Compliance, Accurate, Financial Report